2012
DOI: 10.1002/meet.14504901279
|View full text |Cite
|
Sign up to set email alerts
|

Mobile web interface of academic libraries

Abstract: More and more academic libraries are offering their services via a mobile web platform. This study examined the current status of the mobile web interface of academic libraries in terms of their usability and tried to suggest an effective mobile service design for academic libraries. Seventy‐six mobile academic library web sites were identified. Their first pages were captured and their menu systems were analyzed for different aspects, such as frequently appearing menu items, a search box and search links, URL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Library hours, contact information, and account access were also found at 81.8 percent of the sites with mobile access (Canuel and Crichton, 2011). Han and Jeong (2012) also published a brief study of mobile web interfaces at 76 academic library web sites. While the study focussed on usability of the sites, and only looked at the first page of each, the authors compiled a list of the most frequently appearing menu items that they found.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Library hours, contact information, and account access were also found at 81.8 percent of the sites with mobile access (Canuel and Crichton, 2011). Han and Jeong (2012) also published a brief study of mobile web interfaces at 76 academic library web sites. While the study focussed on usability of the sites, and only looked at the first page of each, the authors compiled a list of the most frequently appearing menu items that they found.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In total, 17 items were noted with varying frequency; links to searching the online catalog were most commonly found on the initial menu (86 percent), followed by hours (80 percent), locations/maps (59 percent), and contact us or contact information (53 percent). For their own purposes, the authors recommended nine items that should be found on a first page menu of mobile web sites that they determined would enhance that site's usability (Han and Jeong, 2012). While this study lacks depth, as the authors only surveyed the first menu page of mobile web sites and used the US News and World Report rankings for their data pool, it is useful as a list of what is actually found on mobile websites, rather than the otherwise somewhat selective lists of other studies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A dichotomy between the need for services as reported by the users and the actual availability of that service was found in a survey of the usability of mobile web interfaces of academic libraries (Canuel and Crichton, 2011). In the rush to provide mobile services, Han and Jeong (2012) concluded, libraries were neglecting the needs of those they were trying to serve by not asking the users.…”
Section: Service Surveysmentioning
confidence: 99%
“…Baker Evans (2011) surveys expert users about mobile usage and upcoming trends they identified that would take advantage of mobile technology. Hyejung Han and Wooseob Jeong (2012) examine the gap between users' needs and academic libraries' mobile offerings through an extensive survey. Many studies detail results from some form of mobile or e-reader usability testing (Aaltonen et al 2011;Bowman 2012;Hegarty and Wustemann 2011;Miller et al 2013;Paterson and Low 2011;Pendell and Yeh 2012;Tidal 2013;).…”
Section: Mobile Usabilitymentioning
confidence: 99%